Genetic Alchemy unveiled: MicroRNA-mediated gene therapy as the Artisan craft in the battlefront against hepatocellular carcinoma—a comprehensive chronicle of strategies and innovations - Murshed, Abduh; Alnoud, Mohammed A. H.; Ahmad, Saleem; Khan, Safir Ullah; Alissa, Mohammed; Alsuwat, Meshari A.; Ahmed, Ahmed Ezzat; Khan, Munir Ullah (Frontiers in Genetics, 2024)
Investigating therapeutic miRNAs is a rewarding endeavour for pharmaceutical companies. Since its discovery in 1993, our understanding of miRNA biology has advanced significantly. Numerous studies have emphasised the disruption of miRNA expression in various diseases, making them appealing candidates for innovative therapeutic approaches. Hepatocellular carcinoma (HCC) is a significant malignancy that poses a severe threat to human health, accounting for approximately 70-85% of all malignant tumours. Currently, the efficacy of several HCC therapies is limited.Alterations in various biomacromolecules during HCC progression and their underlying mechanisms provide a basis for the investigation of novel and effective therapeutic approaches. MicroRNAs, also known as miRNAs, have been identified in the last twenty years and significantly impact gene expression and protein translation. This atypical expression pattern is strongly associated with the onset and progression of various malignancies. Gene therapy, a novel form of biological therapy, is a prominent research area. Therefore, miRNAs have been used in the investigation of tumour gene therapy. This review examines the mechanisms of action of miRNAs, explores the correlation between miRNAs and HCC, and investigates the use of miRNAs in HCC gene therapy.